The Nature-Related Influence of College Students English-Speaking Anxiety in Indonesia - Willy Andriani; Maulina Maulina; Faridawati Faridawati; Analiza Tanghal; Titin Rahmiatin Rahim; Anwar Said (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2023)
The nature influence of speaking anxiety on foreign language (FL) learning settings has been established. In addition, research acknowledges the relevance of speaking performance in affecting individual predisposition to experience anxious feelings. However, few studies examine the Indonesian college students' anxiety influencing factors, mainly when speaking English. Data strategies employed a parallel design combining quantitative and qualitative methods mixing a closed-ended Likert-scale questionnaire with an in-depth interview. Twenty-eight college students responded online via Google Form to the questionnaire, while in addition, the in-depth interviews lasted 45-60 minutes with six college students. The results indicate that learning situations in classroom activities revolve around how teachers teach, college students' self-confidence, belief in language learning experiences, and excessive learning material are nature-related prominence factors of college students' anxiety in speaking English. In contrast, a lack of college students' preparation has no effect. Examined are the means through which this research contributes to the advancement of understanding and comprehension of previously unidentified components that influence college students' speaking anxiety.